2013
DOI: 10.1371/journal.pone.0063830
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Case Detection for Malaria Elimination: Real-Life Experience from an Ongoing Program in Swaziland

Abstract: As countries move towards malaria elimination, methods to identify infections among populations who do not seek treatment are required. Reactive case detection, whereby individuals living in close proximity to passively detected cases are screened and treated, is one approach being used by a number of countries including Swaziland. An outstanding issue is establishing the epidemiologically and operationally optimal screening radius around each passively detected index case. Using data collected between Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
3
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(168 citation statements)
references
References 20 publications
8
153
3
4
Order By: Relevance
“…In addition to evaluating epidemiological indicators, programs can evaluate their operational efficiency using simple, key indicators of programmatic performance; e.g., the proportion of cases recorded and investigated within 7 days of presentation of the index case for evaluating RACD. Similarly, assuming global positioning system (GPS) coordinates are collected, the proportion of households covered for both RACD and PACD can be estimated using freely available satellite imagery [54]. Costs of campaigns should be recorded to allow assessment of cost-effectiveness to enable comparison with other interventions and to assess long-term financial feasibility.…”
Section: Considerations For Successful Acd Implementationmentioning
confidence: 99%
“…In addition to evaluating epidemiological indicators, programs can evaluate their operational efficiency using simple, key indicators of programmatic performance; e.g., the proportion of cases recorded and investigated within 7 days of presentation of the index case for evaluating RACD. Similarly, assuming global positioning system (GPS) coordinates are collected, the proportion of households covered for both RACD and PACD can be estimated using freely available satellite imagery [54]. Costs of campaigns should be recorded to allow assessment of cost-effectiveness to enable comparison with other interventions and to assess long-term financial feasibility.…”
Section: Considerations For Successful Acd Implementationmentioning
confidence: 99%
“…Reactive case detection, whereby households within an established radius surrounding a symptomatic positive index case are screened, is also increasingly being used as a strategy that bridges passive and active surveillance [59,60,61]. Many of these efforts are applying molecular methods to find and treat asymptomatic infections [23,62,63,64].…”
Section: Sparse Data Exist From Elimination Efforts Using Active Survmentioning
confidence: 99%
“…Several projects have explored screening of neighbouring households at varying radii around an index house. For example, studies in Sri Lanka [13] and Swaziland [14, 15] led to a suggested 1-km radius around index households for RCD. Modelling work from Zanzibar suggested that RCD would need to target approximately 100 neighbouring households around each identified case in order to halt transmission [16].…”
Section: Introductionmentioning
confidence: 99%